Aerobic conditioning for team sport athletes - Stone, N. M.; Kilding, A. E. (Sports Medicine, 2009)
Team sport athletes require a high level of aerobic fitness in order to generate and maintain power output during repeated high-intensity efforts and to recover. Research to date suggests that these components can be increased by regularly performing aerobic conditioning. Traditional aerobic conditioning, with minimal changes of direction and no skill component, has been demonstrated to effectively increase aerobic function within a 4- to 10-week period in team sport players. More importantly, traditional aerobic conditioning methods have been shown to increase team sport performance substantially. Many team sports require the upkeep of both aerobic fitness and sport-specific skills during a lengthy competitive season. Classic team sport trainings have been shown to evoke marginal increases/decreases in aerobic fitness. In recent years, aerobic conditioning methods have been designed to allow adequate intensities to be achieved to induce improvements in aerobic fitness whilst incorporating movement-specific and skill-specific tasks, e.g. small-sided games and dribbling circuits. Such 'sport-specific' conditioning methods have been demonstrated to promote increases in aerobic fitness, though careful consideration of player skill levels, current fitness, player numbers, field dimensions, game rules and availability of player encouragement is required. Whilst different conditioning methods appear equivalent in their ability to improve fitness, whether sport-specific conditioning is superior to other methods at improving actual game performance statistics requires further research.